Age-specific and sex-specific reference intervals for non-fasting lipids and apolipoproteins in 7260 healthy Chinese children and adolescents measured with an Olympus AU5400 analyser: a cross-sectional study - Junjie Liu; Yanpeng Dai; Enwu Yuan; Yushan Li; Quanxian Wang; Linkai Wang; Yanhua Su (BMJ Open)
Aims Ethnic, demographic, lifestyle, genetic and environmental factors influence lipids and apolipoproteins. The aim of this study was to establish age-specific and gender-specific reference intervals for non-fasting lipids and apolipoproteins in healthy Chinese children and adolescents.Methods This study followed the Clinical and Laboratory Standards Institute EP28-A3c guidelines. Non-fasting samples were collected from 7260 healthy Chinese children and adolescents, and they were analysed using the Olympus AU5400 analyser for: triglycerides, total cholesterol (TC), high-density lipoprotein cholesterol, low-density lipoprotein cholesterol (LDL-C), apolipoprotein A1 and apolipoprotein B (ApoB). The age-related and gender-related reference intervals were partitioned using the Harris-Boyd method. The non-parametric method was used to establish the lower limit (2.5th percentile) and the upper limit (97.5th percentile) for the reference intervals. The 90% CIs for the lower and upper limits were also calculated.Results Based on the Harris-Boyd method, gender partitions were required for TC, LDL-C and ApoB. Age differences were observed for all analytes. Paediatric reference intervals were established for non-fasting lipids and apolipoproteins based on a large population of healthy children and adolescents.Conclusions Previously used reference intervals did not take age and gender into account. These age-specific and gender-specific reference intervals established in this study may contribute to improved management and assessment of paediatric diseases.